Nutrition in Pediatric Kidney Disease - Román-Ortiz, Elena; Mendizábal-Oteiza, Santiago; Codoñer-Franch, Pilar (Journal of Child Science, 2018)
Nutrition has a major impact on the health of children with chronic kidney disease (CKD). Special diets and additional replacement therapies may be chosen according to the specific renal disease. Persistent low-grade inflammation, which contributes to CKD-associated cardiovascular and all-cause mortality, protein-energy wasting, oxidative stress, acidosis, chronic and recurrent infections, and altered metabolism of adipose tissue may result from dietary deficits and are important targets for nutritive intervention. Therefore, many guidelines have been developed regarding nutrient intake adequation to assist pediatricians treating these children. Acute kidney injury (AKI) has multifactorial etiology and complicated clinical course that may ultimately necessitate renal replacement. AKI presents unique treatment challenges because of associated metabolic derangements, difficulties in nutrient requirement estimation, the negative effects of renal replacement therapy, and the complex effects on nutrient balances. Maintenance of protein balance in such conditions requires adequate energy and protein intake, especially during acute illnesses. Malnutrition in pediatric AKI has been linked to increased morbidity and mortality. However, the recommended nutritional requirements for this condition are less precise than for CKD. A complete assessment of pediatric kidney disease requires evaluation of growth, body composition, abnormal sodium loss, acid-base status, and dietary intake, particularly for children with renal insufficiency. Nutritional support should also provide adequate amounts of energy, macronutrients, and micronutrients for normal growth and development.
Keywords: kidney; chronic kidney disease; acute kidney injury; nutrition; children